1999
DOI: 10.1093/jnci/91.17.1468
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8 Seropositivity and Risk of Kaposi's Sarcoma and Other Acquired Immunodeficiency Syndrome-Related Diseases

Abstract: Approximately one third of individuals co-infected with HIV/HHV8 developed KS within 10 years after HIV seroconversion. Progression to KS increased with time after HIV seroconversion. Higher antibody titers to HHV8 appear to be related to faster progression to KS but not to other AIDS-defining diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 36 publications
3
76
0
2
Order By: Relevance
“…KS is the most common neoplasm in AIDS patients (5,6). The KSHV genome encodes multiple molecules that trigger cell proliferation and induce tumor formation, recapitulating some key pathological features of KSHV-associated malignancies.…”
mentioning
confidence: 99%
“…KS is the most common neoplasm in AIDS patients (5,6). The KSHV genome encodes multiple molecules that trigger cell proliferation and induce tumor formation, recapitulating some key pathological features of KSHV-associated malignancies.…”
mentioning
confidence: 99%
“…Prospective data are lacking, although a study of HIV infected people in Italy suggested that anti-KSHV antibody titres may be persistently high even before the diagnosis of Kaposi's sarcoma, based on the observation of 21 cases of the tumour (Rezza et al, 1999). Data presented here confirm, on substantially larger numbers of cases, that anti-KSHV antibodies are detectable before the diagnosis of the tumour and that the subsequent risk of Kaposi's sarcoma increases with increasing antibody titres (this is true for latent and lytic antibodies).…”
Section: Discussionmentioning
confidence: 99%
“…However, results presented here in relation to KSHV antibody titres are in accord with those reported by Sitas et al (1999) from a case -control study of black South African cancer patients. Furthermore, in a cohort study of HIV-infected men in Europe, Rezza et al (1999) showed that high titres of anti-KSHV antibodies were predictive of the subsequent development of Kaposi's sarcoma among KSHV-infected individuals. These prospective data, together with the fact that the clinical burden of tumour lesions is independent of the titre of anti-KSHV antibodies (Table 1), argue against the possibility that high titres of antibodies against KSHV latent nuclear antigens result from the presence of Kaposi's sarcoma lesions.…”
Section: Discussionmentioning
confidence: 99%